(3MGTjI GdYOIs - (3GdbRhjfj, Ndjd Hf GdZGRj (B, (3J (B1089 (3g`s
(3ChdgG (B:s
.. (3cGf cfbhVG HYdeg JYGdi HPGJg hHGdeYOheGJ hEf CQGO Cfg hGLH GdeWGHbI dYdeg agh UMjM hdG jdRe efg LHQ dCfg YGde HeG SjhLO hdjS HeLHhQ hPdc dCf gPG GdhLhH hLOhH dGMb (B..s
(3BNQgG (B:s
... (3deG aj GdYfGjI GdEdgjI GdeSeGI HGdYfGjI GdChdi hGdYfGjI YHGQI Yf EMGWI Yde Gddg JYGdi HGdcd Ydi eG gh Ydjg EMGWI JGeI afSHI GdbVGA Edi GdYfGjI cfSHI GdbOQ Edi GdbVGA (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\321s
(3GdPQjYI (B6\403s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs